EVOLVING MASCULINITIES IN THE LANGUAGE OF WHY WOMEN KILL (2019): FROM PATRIARCHAL DOMINATION TO ADAPTIVE IDENTITY - Siti Safrotul Machrusya; Ephrillia Noor Fitriana (Universitas PGRI Palembang, 2026)
This study aims to examine how evolving masculinities are constructed through language in Why Women Kill (2019), focusing on the male characters Rob, Karl, and Eli. Employing a qualitative approach, the study uses dialogue transcripts and selected scenes from all ten episodes of the first season as the primary data. The analysis is conducted through coding, interpretation, and conclusion drawing, guided by Raewyn Connell’s theory of masculinity, particularly the concepts of hegemonic masculinity and crisis tendencies. The findings demonstrate that the characters’ language reflects three distinct forms of masculinity across the historical settings of 1963, 1984, and 2019. Rob’s language reinforces hegemonic masculinity through patriarchal authority, control, and gender hierarchy. Karl’s language reflects subordinate masculinity by negotiating social expectations and challenging heteronormative ideals. Meanwhile, Eli’s language represents adaptive masculinity through emotional openness, egalitarian communication, and mutual care. The study further reveals that crisis tendencies in power relations, production relations, and cathexis are linguistically expressed through the characters’ interactions, illustrating the transformation of masculine identities in response to changing social and cultural contexts. This research contributes to the fields of language, gender, and masculinity studies by demonstrating how language functions as a medium for constructing, maintaining, and transforming masculine identities in media discourse. The novelty of this study lies in its examination of the evolution of masculinity through linguistic representation in Why Women Kill (2019), an aspect that has received limited scholarly attention compared with previous studies that primarily emphasize female characters and feminist perspectives.